Conducting clinical trials in five Eastern European countries (EU-EECs) with a focus on Bulgaria - Tatyana Benisheva; Dimitar Milkov; Valentin Kopanarov; Ivaylo Ivanov; Dimitar Dimitrov; Veselina Todorova; Nigyar Dzhafer; Iva Chavkova; Lyubina Todorova; Lena Gebert (Biotechnology & Biotechnological Equipment)
Data for ongoing and completed clinical trials (Phases I-III) were extracted from the European Union Clinical Trials Register for five EU-EECs (Bulgaria, Hungary, Poland, Romania and Slovakia) (from January 1, 2012 to September 30, 2022). Based on the almost 11-year period Poland (n = 4134) and Hungary (n = 3845) represent the largest share of trials, with over 250–300 ongoing and completed clinical trials a year. Bulgaria (with a population of 7 mill. inhabitants) has a lower number of completed and ongoing trials (n = 2049) versus Poland and Hungary, which, however, have much larger populations (Poland − 38 mill., Hungary − 9.8 mill.). Slovakia (5.5 mill. inhabitants), has 67% fewer ongoing and completed clinical trials (n = 1374) than Poland, while Hungary and Bulgaria also have more trials than Slovakia (64% and 33% respectively). The prevalence of trials in all EEC countries was calculated per 100,000 inhabitants, where Hungary (n = 39) ranks first, while Bulgaria (n = 29) is ahead of Slovakia (n = 25), Poland (n = 11) and Romania (n = 5). The ongoing and completed clinical trials conducted in the ten EU-EECs (n = 19030) have shown remarkable expansion over the past decade, accounting for a large share (26.3%) of all EU-wide trials (n = 72215) for the referenced period. The leader of the western EU countries, in terms of trials per 100,000 inhabitants is Denmark (n = 56) followed by Belgium (n = 44), Austria (n = 33), Finland (n = 30) and the Netherlands (n = 30). These results demonstrate that the number of completed and ongoing trials does not correspond to the size of a country’s population.